2021
DOI: 10.1021/acs.molpharmaceut.1c00716
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Praziquantel/Cyclodextrin Inclusion Complexation by NMR and LC-HRMS/MS: Mechanism, Solubility, Chemical Stability, and Degradation Products

Abstract: Praziquantel (PZQ) is a biopharmaceutical classification system (BCS) class II anthelmintic drug characterized by poor solubility and a bitter taste, both of which can be addressed by inclusion complexation with cyclodextrins (CD). In this work, a comprehensive investigation of praziquantel/cyclodextrin (PZQ/CD) complexes was conducted by means of UV–vis spectroscopy, spectrofluorimetry, NMR spectroscopy, liquid chromatography-high-resolution mass spectrometry (LC-HRMS/MS), and molecular modeling. Phase solubi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…This value is consistent with previous experimental results on a similar organic molecule (tryptophan) trapped in a clay-based material ( D ∼ 5 × 10 −11 cm 2 s −1 ) [46]. It is five orders of magnitude smaller than the diffusion coefficient of praziquantel dissolved in water [47,48].…”
Section: Drug Adsorbed In the Clay's Interlayer Spacesupporting
confidence: 92%
“…This value is consistent with previous experimental results on a similar organic molecule (tryptophan) trapped in a clay-based material ( D ∼ 5 × 10 −11 cm 2 s −1 ) [46]. It is five orders of magnitude smaller than the diffusion coefficient of praziquantel dissolved in water [47,48].…”
Section: Drug Adsorbed In the Clay's Interlayer Spacesupporting
confidence: 92%
“…CD complexes can be used to release biologically active compounds under specific conditions [ 31 , 32 , 33 ]. A recent study showed that the complexation with β-CD enhanced the therapeutic efficiency of praziquantel from 59% (for the plain drug) to 99% (for the β-CD complex) [ 34 ]. Moreover, studies with the essential oil of ocimum plant showed a low absorption giving a maximum % inhibition of edema equal to of 16%, while after its complexation with SBE-β-CD/HP-β-CD a higher absorption was observed achieving more than 50% inhibition of edema [ 35 ].…”
Section: Introductionmentioning
confidence: 99%